Decarbonizing Seaport Maritime Traffic: Finding Hope - Seyed Behbood Issa-Zadeh; Claudia Lizette Garay-Rondero (World)
The maritime transport industry contributes around 3% to worldwide CO2 emissions, with 2023 emissions projected to be approximately 58 billion tons. Consequently, to attain decarbonization objectives, the implementation of effective reduction measures in maritime operations, especially at seaports as significant contributors, is essential. On the other hand, seaport operations are categorized into two main areas: land logistics, encompassing cargo handling, storage, customs processing, and inland transportation, and maritime logistics, which includes vessel traffic management, berth allocation, cargo loading and unloading, and fuel and maintenance services. While land logistics’ decarbonization has been extensively studied, maritime logistics operations, accounting for about 60% of port CO2 emissions, remain underexplored. Their progress relies on regulations, cleaner fuels, and digital solutions; yet high costs and slow adoption pose significant challenges. As a result, this study employed PRISMA-ScR methodology to select relevant research resources and validate global reports from international organizations, enhancing transparency and providing practitioners and experts with a comprehensive analysis of seaport maritime emissions, as well as decarbonization initiatives. This study analyzes the future trajectory of the initiative based on current data, evaluating its potential benefits and systematically reviewing recent literature. It explores decarbonization strategies in maritime operations, emphasizing regulations, cleaner fuels, and digital solutions while highlighting challenges such as high costs and slow adoption. Key issues examined include maritime border delineation, infrastructure constraints, technological advancements, regulatory barriers, and the opportunities that decarbonized seaports offer to ports and their surrounding regions.